2020
DOI: 10.1007/s40843-020-1432-7
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange membranes with eight flexible side-chain cations for improved conductivity and alkaline stability

Abstract: Increasing the local charge density of flexible side-chain cations in the hydrophilic segments of anion exchange membranes (AEMs) is helpful for improving their properties. However, due to limitations of structural design strategies and available synthetic methods, very few AEMs with more than four flexible side-chain cationic groups in hydrophilic segments have been reported. In order to further improve the hydroxide conductivity, alkaline stability and dimensional stability, herein we report a series of AEMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The properties of AEMs are closely influenced by some structural factors, including the types of cationic groups, the linking ways of cations with polymer backbone, and their aggregation distribution in structural units. , In the previous study of high-performance AEMs, we designed and reported a class of AEMs containing eight flexible piperidine ions based on poly­(aryl ether sulfone)­s . It is found that the combination of densely flexible side chains and piperidinium ions in the hydrophilic structural units of AEMs is very effective to improve their hydroxyl conductivity and alkaline stability.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of AEMs are closely influenced by some structural factors, including the types of cationic groups, the linking ways of cations with polymer backbone, and their aggregation distribution in structural units. , In the previous study of high-performance AEMs, we designed and reported a class of AEMs containing eight flexible piperidine ions based on poly­(aryl ether sulfone)­s . It is found that the combination of densely flexible side chains and piperidinium ions in the hydrophilic structural units of AEMs is very effective to improve their hydroxyl conductivity and alkaline stability.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of AEMs have a close relationship with polymer structures, [32,33] including the category and structure of cationic group, the composition and spatial structure of the polymer backbone and the type of linkage between the ionic group and polymer backbone. [34][35][36] Among these factors, the structure of cationic group is one of the key factor to be considered next to the polymer backbone, which has a profound impact on the alkaline resistance stability and hydroxide conductivity of AEMs. Quaternary ammonium (QA) cations are the most studied functional cations for AEMs in the past several years because of their convenience, maturity and ease, and low cost of the synthesis process.…”
Section: Progress In High-performance Anion Exchange Membranes Based On the Design Of Stable Cations For Alkaline Fuel Cellsmentioning
confidence: 99%
“…The hydrophobicity of the long chain tends to form more efficient hydrophilic phase topology and to increase the anionic conductivity and/or chemical stability of the ammonium group [8,17,19,34e42]. In the case of the QA group, the graft (also named side chain) can be tuned by increasing the length of the intermediate alkyl chain (spacer unit) or by substituting one of the methyl group for a longer chain (extender chain) [17,18,37,39,43,45]. Coarse grained MD with a PPO (polyphenylene oxide) backbone show that hydrophilic morphology can be designed by the pattern of the tethering from the lamellar structure to a more interconnected one [46,47].…”
Section: Introductionmentioning
confidence: 99%